2011
DOI: 10.1366/10-06184
|View full text |Cite
|
Sign up to set email alerts
|

On Sample Preparation for Surface-Enhanced Raman Scattering (SERS) of Bacteria and the Source of Spectral Features of the Spectra

Abstract: The characterization, detection, and identification of bacteria using surface-enhanced Raman scattering (SERS) spectroscopy is drawing considerable attention due to its ability to provide rich intrinsic molecular information about molecules and molecular structures in close proximity to noble metal surfaces. However, sample preparation methods and experimental conditions must be carefully evaluated in order to obtain healthy, interpretable, and comparable results. In this study, several bacterial species inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 32 publications
5
69
0
Order By: Relevance
“…The fluorescence quenching is another advantage of the technique to mention. Due to its remarkable and versatile features, this technique has been used heavily for detection and identification of bacteria [15][16][17][18][19][20][21], cells [22], tissues [23], and biomolecules [24] within the last decade. Therefore, SERS has a potential to be used for diagnostic purposes in clinical settings and several studies have been published on the way to realize this goal [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence quenching is another advantage of the technique to mention. Due to its remarkable and versatile features, this technique has been used heavily for detection and identification of bacteria [15][16][17][18][19][20][21], cells [22], tissues [23], and biomolecules [24] within the last decade. Therefore, SERS has a potential to be used for diagnostic purposes in clinical settings and several studies have been published on the way to realize this goal [25].…”
Section: Introductionmentioning
confidence: 99%
“…There is a consensus among bacteria-SERS community that the origins of the spectra are bacteria cell wall components and some metabolites, which reside in the cell wall during spectral acquisition [16,30]. When the effective plasmon field of silver nanoparticles (up to 4 nm) is considered, this is highly logical.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3F shows the SERS spectra of captured S. aureus on the are seen clearly and in accordance with those in previous reports categorized in Table S1. 51,52 The SERS signal becomes weak as the S. aureus concentration decreases. In addition, the major Raman peaks of S. aureus can be observed at the concentration of 10 6 …”
Section: Enrichment Performance and Sers Ability Of Fe 3 O 4 @Ag-van mentioning
confidence: 99%
“…51,52 It is observed that the SERS signal becomes weak as the concentration of bacteria decreases. The strongest peak observed at 733 cm 2 cells/mL) suggests that the low limit of detection of the combined system for S. aureus detection (5×10 2 cells/mL) lies within a large dynamic detection range ( Figure S7).…”
mentioning
confidence: 99%
“…The origin of the bands that appeared on the SERS spectra of bacteria was independently investigated by two groups. Kahraman et al demonstrated that the SERS spectra obtained from a bacterial sample after several washing steps originate from the bacterial structures on the bacteria wall with some contribution from metabolites released during the sample preparation, mixing, and drying [147]. Premasiri et al showed that the bacteria grown in different culture media resulted with the same SERS spectrum indicating the source of spectral features on the spectrum were from bacteria [148].…”
Section: Detection Identification and Characterization Of Biomacrommentioning
confidence: 99%